Tobacco use and incident sleep parameters among a rural ageing population in South Africa - Pengpid S. (2023)
INTRODUCTION Tobacco use may be associated with incident insomnia. The aim of the study was to investigate the association between tobacco use and incident sleep parameters in a longitudinal study in South Africa. METHODS Longitudinal data from two consecutive waves of middle-aged and older adults in 2014–2015 (n=5059) and 2018–2019 (n=4176) in rural South Africa were analyzed. Tobacco use and sleep parameters were assessed by self-report. The associations between tobacco use and incident sleep parameters were estimated with multivariable logistic regression. RESULTS The prevalence of baseline sleep parameters was poor sleep quality 6.5%, sleep disturbance 13.6%, restless sleep 32.9%, and breathing stops 7.0%. In the fully adjusted model for people without poor sleep quality at baseline, daily tobacco smoking, smoking ≥10 units of tobacco products, current tobacco use and current smokeless tobacco use did not increase the odds of incident poor sleep quality. Smoking ≥10 units of tobacco products in a day (AOR=3.83; 95% CI: 1.77–8.28), current tobacco use (AOR=1.65; 95% CI: 1.09–2.51), and daily tobacco smoking (AOR=2.16; 95% CI: 1.15–4.07), were significantly positively associated with incident sleep disturbance. Furthermore, incident restless sleep was significantly positively associated with smoking ≥10 units of tobacco products in a day (AOR=3.97; 95% CI: 1.18–13.37), current smokeless tobacco use (AOR=2.78; 95% CI: 1.17–6.62) and current tobacco use (AOR=2.00; 95% CI: 1.00–4.00). Incident breathing stops were significantly positively associated with daily smoking tobacco (AOR=2.08; 95% CI: 1.11–3.34), smoking 1–9 units of tobacco products in a day (AOR=2.17; 95% CI: 1.20–3.94), and current tobacco use (AOR=1.77; 95% CI: 1.16–2.72). CONCLUSIONS Higher tobacco use was independently associated with incident sleep disturbance, incident restless sleep, and incident breathing stops, but not with incident poor sleep quality.